Story discourse and use of mental state language between mothers and school‐aged children with and without visual impairment. Issue 6 (9th September 2013) - Tadić, Valerija; Pring, Linda; Dale, Naomi
Abstract: Background: Lack of sight compromises insight into other people's mental states. Little is known about the role of maternal language in assisting the development of mental state language in children with visual impairment (VI). Aims: To investigate mental state language strategies of mothers of school‐aged children with VI and to compare these with mothers of comparable children with typically developing vision. To investigate whether the characteristics of mother–child discourse were associated with the child's socio‐communicative competence. Methods & Procedures: Mother–child discourse with twelve 6–12‐year‐old children with VI was coded during a shared book‐reading narrative and compared with 14 typically sighted children matched in age and verbal ability. Outcomes & Results: Mothers of children with VI elaborated more and made significantly more references to story characters' mental states and descriptive elaborations than mothers of sighted children. Mental state elaborations of mothers in the VI group related positively with the level produced by their children, with the association remaining after mothers' overall verbosity and children's developmental levels were controlled for. Frequency of maternal elaborations, including their mental state language, was related to socio‐communicative competence of children with VI. Conclusions & Implications: The findings offer insights into the potential contribution of maternal verbal scaffolding to mentalistic language and social–communicative competences of children with VI.